2009
DOI: 10.1002/jrs.2370
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of lead(II) oxalate

Abstract: The infrared and Raman spectra of anhydrous lead oxalate (PbC 2 O 4 ) were recorded and discussed on the basis of its structural peculiarities. Some comparisons with other previously investigated metallic oxalates were made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…6a). The Raman band at 486 cm −1 and 498 cm −1 are the ν 3 , δ s (O-C-O) mode in the lead oxalate, the 854 cm −1 and 891 cm −1 band are assigned to the ν 2 , ν(C-C), 1436 cm −1 and 1478 cm −1 are assigned to the ν 1 , ν s (C-O), and 1588 cm −1 is assigned to the ν 10 , ν s (C-O) 29 . Further, the peaks in the XRD pattern, 18.65°, 19.57°, 21.27°, 23.71°, 26.29°, 32.51°, 39.05°, and 51.26°, correspond to the diffraction crystal planes of lead oxalate from diffraction software ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6a). The Raman band at 486 cm −1 and 498 cm −1 are the ν 3 , δ s (O-C-O) mode in the lead oxalate, the 854 cm −1 and 891 cm −1 band are assigned to the ν 2 , ν(C-C), 1436 cm −1 and 1478 cm −1 are assigned to the ν 1 , ν s (C-O), and 1588 cm −1 is assigned to the ν 10 , ν s (C-O) 29 . Further, the peaks in the XRD pattern, 18.65°, 19.57°, 21.27°, 23.71°, 26.29°, 32.51°, 39.05°, and 51.26°, correspond to the diffraction crystal planes of lead oxalate from diffraction software ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Upon coordination of the oxalate as a mono-oxalate species, the symmetry species is reduced to C 2v or D 2h . Assignments of Raman spectra of oxalic acid and oxalates have been reported in previous studies (Chang and Huang, 1997;D'Antonio et al, 2010;Ebisuzaki and Angel, 1981;Frost, 2004;Mancilla et al, 2009;Moha cekGro sev et al, 2009). According to these literatures, we made the assignments as follows, which are also summarized in Table 1.…”
Section: Assignments Of Raman Bandsmentioning
confidence: 99%
“…The gray dashed line represents the Raman spectrum of iron (II) oxalate dihydrate. (Ebisuzaki and Angel, 1981;Frost, 2004;Frost and Weier, 2003;Mancilla et al, 2009;Moha cek-Gro sev et al, 2009). Previous studies always assigned the Raman shift bands in the range of 1610e1650 cm À1 to the stretching mode of C]O (Frost, 2004;Mancilla et al, 2009 particles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the spectra displayed peaks at~1,440,~1,480, and~1,590 cm −1 , which were assigned to various C─O vibrations of Pb oxalate mineral. [32] Therefore, the characteristic peaks of spot analysis in Figure 3 confirmed that the secondary mineral is Pb oxalate. It should be pointed out that the small (Figure 3a) and large (Figure 3b) Pb oxalate particles demonstrated distinct order (also confirmed after normalization) of the intensities for Raman peaks at~1,440,~1,480, and 1,590 cm −1 , suggesting the variable orientation of the secondary Pb mineral (probably due to different growth stage).…”
Section: Identification Of Pb Secondary Minerals Using Risementioning
confidence: 77%